Erosion Behavior of Metal Nitride Coatings Fabricated by Physical Vapor Deposition - L. R. Zhao; W. R. Chen; X. Z. Ding; X. T. Zeng (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
The effect of deposition defects in metal nitride coatings on erosion behavior is presented. AlCrN, AlTiSiN, TiSiN and TiSiN:MoS2 coatings were fabricated by reactive cathodic arc evaporation and unbalanced magnetron sputtering processes. The microstructure and mechanical properties of the coatings were characterized by X-ray diffraction, scanning electron microscopy and nanoindentation, and the erosion property was assessed by solid particle impingement testing. The erosion characteristics on the coating surface and cross section were analyzed and correlated to the defects, which played an important role by promoting formation of erosion pits.